Comparative analysis of the composition of essential oils from the needles, twigs and berries of Juniperus chinensis L. in Korea - Kandhasamy Sowndhararajan, Min Seo, Songmun Kim (Journal of Applied Pharmaceutical Science, 2016)
The essential oil constituents from the needles, twigs and berries of Juniperus chinensis from Korea were investigated by gas chromatography-mass spectrometry (GC-MS). The essential oils from the different plant parts were obtained by steam distillation and the yields were 0.34, 0.11 and 0.12% (v/w), respectively. The GC-MS analysis revealed the identification of 36 different components from needles, twigs and berries, which were mostly monoterpene hydrocarbons (42.05-48.15%) followed by oxygenated monoterpenes (28.53-39.92%).Among the 36 components, 17 components were identified in all the three essential oils. The components such as bornyl acetate (2.85 – 20.70%), sabinene (10.23 – 18.13%), α-pinene (5.80 – 16.26%), terpinen-4-ol (5.98 – 31.10%), limonene (3.98 – 6.96%), β-pinene (3.05 – 4.39%), γ-terpinene (2.24 – 8.36%), α-elemol (1.74 – 4.77%) and α-cadinol (2.49 – 3.39%) were detected as the major components in the essential oils from the three different parts of J. chinensis. The main differences between the three essential oils can be referred to terpinen-4-ol and bornyl acetate. The essential oil of the berries contained the highest level of terpinen-4-ol (31.10%) than needles (7.51%) and twigs (5.98%). On the other hand, bornyl acetate content was very less in berries (2.85%) when compared with twigs (20.70%) and needles (16.43%).
Keywords: Berry, Essential oil, Juniper, Juniperus chinensis, Needle.